Pengaruh Ekspor, Impor dan Utang Luar Negeri Terhadap Pertumbuhan Ekonomi di Indonesia Pada Tahun 2013 – 2022 - Haris Istiawan Khan; Komala Sari; M. Kurniawan (Journal Economic Excellence Ibnu Sina, 2024)
This research was conducted with the aim of determining the influence of exports, imports and foreign debt on economic growth in Indonesia for the period 2013 - 2022. The measurement of export, import and foreign debt variables is explained through the position of exports, imports and government foreign debt, economic growth is measured through economic growth in the secondary sector. Data obtained via download on the websites of Bank Indonesia and the Central Statistics Agency. The analytical tool used is Eviews 12 with the help of Eviews 12 data processing. The results of the structural model evaluation show that exports have a negative and insignificant effect on economic growth, imports have a negative and insignificant effect on economic growth and foreign debt has a positive and significant effect on economic growth.